2019
DOI: 10.1097/ccm.0000000000003841
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Compartment Profiling of Bacterial and Host Metabolites Identifies Intestinal Dysbiosis and Its Functional Consequences in the Critically Ill Child

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…Studies conducted in mice have shown that gut bacteria alter the distribution of free amino acids in the gastrointestinal tract and affect the bioavailability of amino acids for the host 48 . When the gut microbiota is healthy (eubiotic status), a trophic network is maintained that is suitable for the fermentation of substances present in the intestine, but when the gut microbial balance is disrupted (dysbiotic status), this trophic network is disrupted and the community shows poor fermentation efficiency 49 . Thus, higher concentrations of amino acids in the intestine are thought to be the result of incomplete fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in mice have shown that gut bacteria alter the distribution of free amino acids in the gastrointestinal tract and affect the bioavailability of amino acids for the host 48 . When the gut microbiota is healthy (eubiotic status), a trophic network is maintained that is suitable for the fermentation of substances present in the intestine, but when the gut microbial balance is disrupted (dysbiotic status), this trophic network is disrupted and the community shows poor fermentation efficiency 49 . Thus, higher concentrations of amino acids in the intestine are thought to be the result of incomplete fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently published data suggest that altered gut microbiome in patients receiving broad‐spectrum antibiotics 47,48 may lead to malabsorption of nutrients and thereby contribute to EFI 49 …”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 ] Critical illness is considered one of the major environmental influences that can impact the gut environment. [ 4 ] It is associated with pathophysiological effects causing damage to the intestinal microbiome. These include ischemia, hypoxia and hypotension along with the iatrogenic effects of therapeutic agents and the lack of enteral feeds.…”
Section: Introductionmentioning
confidence: 99%